(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The issue of photography’s copyright was addressed several times in the courts and its importance is not limited to questions of historical-legal. En effect different possibilities of theoretical interpretations of the photography’s nature spring from the way it was treated . It is believe necessary to illustrate the problem by displaying some of the most important processes for the conquest of this right.